Salivary level of RANKL and OPG in chronic periodontitis - Batool H Al-Ghurabi; Sara M Mohssen (College of Dentistry/ University of Baghdad, 2015)
Background: Periodontal diseases are initiated by microbial plaque, which accumulates in the sulcular region and induces an inflammatory response. The Receptor activator of nuclear factor-kappa B ligand / osteoprotegerin (RANKL/OPG) axis is involved in the regulation of bone metabolism in periodontitis, in which an increase in receptor activator of nuclear factor-kappa B ligand or a decrease in osteoprotegerin can tip the balance in favor of osteoclastogenesis and the resorption of alveolar bone that is the hallmark of periodontitis. This study was performed to investigate the role of salivary levels of RANKL and OPG in pathogenesis of chronic periodontitis. Subjects and Methods: Fifty five subjects with chronic periodontitis with ages range from 24-64 years and 25 apparently healthy volunteers their ages and sexes were matched with the patients were participated in this study. Periodontal parameters used in this study were plaque index, gingival index, probing pocket depth, clinical attachment level and bleeding on probing. Saliva samples were collected from all patients and controls. Enzyme-linked immunosorbent assay was carried out for estimation the salivary level of RANKL and OPG in studied groups. Results: The present data revealed that the median salivary levels of RANKL was elevated in patient as compared with control group (P0.05). In contrast the ratio of RANKL/OPG ratio was significantly higher in patients when compared with the ratio in control group. Furthermore, negative significant correlation was noticed between RANKL and OPG. Regarding correlation between salivary (RANKL and OPG) and clinical periodontal parameters, RANKL levels was showed significant positive correlation with each of probing pocket depth and clinical attachment level. Otherwise no association between OPG levels and clinical parameters of periodontitis was found. Moreover; the ratio RANKL/OPG was showed significant positive correlation with each of gingival index, probing pocket depth and clinical attachment level. Conclusion: This study demonstrates that salivary levels of RANKL and OPG play a crucial role in pathogenesis of periodontitis, and the relative RANKL/ OPG ratio appears to be indicative of disease occurrence. Keywords: chronic periodontitis, RANKL, OPG.